MOTIVATION AND ELECTRONIC MEDIA IN LSP TRANSLATION TEACHING - KORDIC, Ljubica (Comparative Legilinguistics, 2019)
Expansion of IT-media in every field of human activity is one of the essential characteristics of modern time. This paper aims at presenting the role of electronic media in teaching translation in the field of law at the University of Osijek, Croatia, and analysing their impact on the motivation of the target group of students in the teaching process. The paper endeavours to provide some insight into the modern teaching practice and to analyse the interconnectedness of the use of electronic media and student motivation rather than to present some empirical research in the field. In the first part of the paper, a theoretical approach to teaching legal translation today is offered. In the main part, teaching legal translation by using modern media is presented on the examples of the Lifelong Learning Programme for Lawyer-Linguists at the Faculty of Law Osijek, and the course on legal translation within the German Language and Literature Studies at the Faculty of Humanities and Social Sciences of Osijek. The usage of electronic media in translation teaching is discussed with reference to the courses Introduction to the Theory of Legal Translation and Online Translation Tools and EU Vocabulary. Specific types of online materials, translation tools and sources are discussed from the point of view of student motivation. New media are also discussed from the perspective of their efficiency at different stages of translation teaching. In the concluding part, application of modern technologies in teaching legal translation is compared with other teaching methods, approaches and techniques. Finally, the author questions using IT as motivation tools in the higher education teaching discourse and argues for application of “moderate approach” in the teaching of legal translation.